Pengaruh Pajak dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Kota Medan - Batubara, Ade Andriani; Rahayu, Fitri; Manik, Lastiara; Anggraini, Rika (Asosiasi Dosen Akuntansi Indonesia, 2023)
Regional taxes and levies are mandatory contributions paid by the community to the government. Therefore, this study aims to see how regional taxes and levies affect the Regional Original Income (PAD) of Medan City. This type of research is quantitative research using the classical assumption test analysis method and multiple linear regression. The type of data used is secondary data obtained from the official DJPK website. The data used are regional taxes (X1), regional levies (X2), and Regional Original Income (Y) with the observation year 2018-2022. The results of the study show that regional taxes have a positive and significant effect on the Regional Original Income of Medan City with a Prob. value of 0.0149 <0.05. While regional levies have a positive but not significant effect on the Regional Original Income of Medan City